Comparative transcriptome analysis of whiteflies raised on cotton leaf curl Multan virus-infected cotton plants - Chen, Ting; Jia, Yanbo; Chen, Jie; Qi, Guojun (Frontiers in Veterinary Science, 2024)
Cotton leaf curl Multan virus (CLCuMuV), a serious viral disease-causative agent in cotton plants in South Asia, is transmitted by Bemisia tabaci cryptic species complex in a persistent-circulative manner. Previous study indicated that Asia II-7 whiteflies could transmit CLCuMuV while Mediterranean (MED) failed to. However, little is known about the genes involved in this process. In this study, Asia II-7 and MED B.tabaci were utilized to determine transcriptomic responses after 48h acquisition access periods (AAPs). As a result, 14,213 and 8,986 differentially expressed genes (DEGs) were identified. Furthermore, DEGs related to the immune system and metabolism of Asia II-7 and MED in response to CLCuMuV-infected plants were identified and analyzed using Gene Ontologies (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG), and the number of related DEGs in MED was lower than that of Asia II-7. The most abundant groups of DEGs between both viruliferous and aviruliferous whitefly species were zf-C2H2 family of transcription factors (TFs). Notably, in comparison to viruliferous MED, Asia II-7 exhibited more DEGs related to cathepsin biosynthesis. Overall, this study provides the basic information for investigating the molecular mechanism of how begomoviruses affect B.tabaci metabolism and immune response either as vector cryptic species or non-vector species.